Integrating Stress Management into Teaching Practices: A Reflective Case Study of Pre-Service Teachers in the SEA Teacher Program - Suciati, Sri; Hana, Laela; Truc, Le Chanh; Ardini, Sukma Nur (Allure Journal, 2025)
This study investigated the stress management strategies during the SEA Teacher program which implemented in teaching. The research questions inquiries: (1) What were the stressors faced by pre-service teachers during the SEA-Teacher Program (2) What strategies did they employ to manage these pressures. The aims of this study were recognized and outlined the pressures faced by these upcoming pre-service teachers during their overseas internship, and clarify the kinds of coping strategies and techniques they utilized. This study was conducted in the Dong Thap, Vietnam. The method is used qualitative approach with descriptive type was employed using questionnaire and interview to collect the data from twelve pre-service teachers who participated in SEA Teacher program. The findings revealed that there was the source of stress which revealed in several key; communication style, pressure of language adaptation, and cultural differences. Furthermore, it focused on the significance of psychological debriefing and organizational assistance in global internship programs for pre-service teachers. Their capacity to handle stress is greatly influenced by elements like social support, readiness, and the pre-service teachers’ ability to reflect on themselves. Considering these results, it is suggested that SEA Teacher program should improve their mental health support. This enhancement could include providing training focused on stress management and developing abilities for effective intercultural communication. Additionally, maintaining steady social support, like mentoring and peer assistance networks, is crucial for aiding pre-service teachers in coping with stress throughout their internship experiences.